2022
DOI: 10.1021/acs.analchem.2c03144
|View full text |Cite
|
Sign up to set email alerts
|

Framework and Spherical Nucleic Acids Synergistically Enhanced Electrochemiluminescence Nanosensors for Rapidly Diagnosing Acute Myocardial Infarction Based on Circulating MicroRNA Levels

Abstract: Acute myocardial infarction (AMI)-related micro-RNAs (miRNAs) in circulating blood have been proved as promising biomarkers for AMI diagnosis. The detection of these miRNAs at ultralow levels usually requires nucleic acid amplification strategies to improve the sensitivity at the cost of time. Given that the first hour after an AMI attack is the golden time for saving AMI patients' lives, shortening the time of ultrasensitive miRNA analysis is of great significance for clinical AMI diagnosis. Toward this goal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…23,24 So we envisage that tethering this aptamer to one of the TTP structures will allow exosomes to be immobilized there for proximity, releasing internal miRNAs that are involved in the ECL reaction on the TTP nanoplatform. 22 Such a proximity effect in principle contributes to the ECL readout, as reported previously. 6,25,26 With this idea in mind, herein we build two TTP structures functionalized with the CD63-binding aptamer 27 and probe strand, respectively, and then conjugate them on one edge to form a dimeric analytical platform (Figure 1), reported with the luminol-H 2 O 2 ECL system catalyzed by covalently heminmodified spherical nucleic acid enzymes (c-SNAzymes).…”
Section: ■ Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…23,24 So we envisage that tethering this aptamer to one of the TTP structures will allow exosomes to be immobilized there for proximity, releasing internal miRNAs that are involved in the ECL reaction on the TTP nanoplatform. 22 Such a proximity effect in principle contributes to the ECL readout, as reported previously. 6,25,26 With this idea in mind, herein we build two TTP structures functionalized with the CD63-binding aptamer 27 and probe strand, respectively, and then conjugate them on one edge to form a dimeric analytical platform (Figure 1), reported with the luminol-H 2 O 2 ECL system catalyzed by covalently heminmodified spherical nucleic acid enzymes (c-SNAzymes).…”
Section: ■ Introductionsupporting
confidence: 58%
“…Based on it, here, we seek to build a dimeric TTP-based analytical platform that integrates exosome capturing and proximity miRNA sensing. It has been demonstrated that exosomes can be captured by a DNA aptamer that specifically binds CD63 proteins on the surface. , So we envisage that tethering this aptamer to one of the TTP structures will allow exosomes to be immobilized there for proximity, releasing internal miRNAs that are involved in the ECL reaction on the TTP nanoplatform . Such a proximity effect in principle contributes to the ECL readout, as reported previously. ,, …”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Electrochemiluminescence (ECL), a powerful optical technology of low background noise, wide dynamic range, and high sensitivity, is being widely used for immunoassays , and DNA probe analyses. , An ECL assay is conducted in either a total-photon-collected or a wavelength-resolved way. The wavelength-resolved ECL is normally conducted with area array detectors, , such as charge-coupled devices , and complementary metal-oxide semiconductors. , Although the dispersion of ECL can enable multiple immunoassays without spectral cross-talk, , the ECL photons at a given wavelength are much less than the total ECL photons. From this point, the commercialized ECL immunoassay is normally conducted in a total-photon-collected way with a photomultiplier tube as a detector. , …”
mentioning
confidence: 99%